2020
DOI: 10.3390/brainsci11010014
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Commercial Cigarette Smoke Produces Psychomotor Sensitization via Hyperstimulation of Glutamate Response in the Dorsal Striatum

Abstract: Cigarette smoke is a highly complex mixture of nicotine and non-nicotine constituents. Exposure to cigarette smoke enhances tobacco dependence by potentiating glutamatergic neurotransmission via stimulation of nicotinic acetylcholine receptors (nAChRs). We investigated the effects of nicotine and non-nicotine alkaloids in the cigarette smoke condensates extracted from two commercial cigarette brands in South Korea (KCSC A and KCSC B) on psychomotor behaviors and glutamate levels in the dorsal striatum. Repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The present study demonstrated that nicotine exposure via cigarette smoke downregulated GLT-1 gene and protein levels in the NAc, while tobacco smoke exposure decreased xCT gene and protein levels in the PFC and the NAc. Ample of evidence links anxiety-like behavior with changes in synaptic activity resulting from dysregulation of glutamatergic function ( Ryu et al, 2021 ). A growing body of evidence demonstrates that glutamate neurotransmission plays a key role in anxiety disorder etiology as well ( Garakani et al, 2006 ; Manhaes et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that nicotine exposure via cigarette smoke downregulated GLT-1 gene and protein levels in the NAc, while tobacco smoke exposure decreased xCT gene and protein levels in the PFC and the NAc. Ample of evidence links anxiety-like behavior with changes in synaptic activity resulting from dysregulation of glutamatergic function ( Ryu et al, 2021 ). A growing body of evidence demonstrates that glutamate neurotransmission plays a key role in anxiety disorder etiology as well ( Garakani et al, 2006 ; Manhaes et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, distinct psychoactive effects have been reported depending on the types of e-cig device (Keamy-Minor et al, 2019;Holt et al, 2021), the experience of e-cig use (Loud et al, 2021), and types of nicotine products (Ryu et al, 2021). For example, Loud and colleagues have described that varying psychoactive effects, including intensifying the current moods, causing an adrenaline rush, and triggering addiction, are elicited by smoking r-cigs or vaping e-cigs in heavy smokers, dual users of regular and electronic cigarettes, and former smokers who quit smoking (Loud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that stimulation of α7 nAChR, which is expressed mainly in the glutamate terminals of the CPu, enhances glutamate release after nicotine exposure ( Engelman and MacDermott, 2004 ; Ryu et al, 2017 ). Challenge exposure to nicotine after withdrawal increases locomotor activity by stimulating α7 nAChR in the CPu of rats ( Ryu et al, 2017 , 2020 ), suggesting that elevation of glutamate release leads to behavioral sensitization. Previous studies have demonstrated that increased phosphorylation of Ser831 in the CPu after cocaine exposure causes the elevation of locomotor activity in rats ( Martínez-Rivera et al, 2017 ; Wang et al, 2017 ; Yang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%